Effect of holding time and removal of seminal plasma on preservation of boar semen at liquid state - TYNGKAN, L; BHUYAN, D; NATH, K C; SAHARIA, J; DUTTA, D J; BISWAS, R K; DAS, A (The Indian Journal of Animal Sciences, 2014)
Effects of 3 holding times and 3 levels of removal of seminal plasma on the quality of Hampshire boar semen during preservation in BTS extender for different periods were studied. The semen samples were held at 24°C prior to extension and preservation. The effect of removal of 0, 50, 75 and 100% of seminal plasma was studied after holding for 5 h by subsequently replacing and extending it with BTS before preservation. The mean sperm motility, live sperm count and intact acrosome were significantly higher at 5 h than at 6 and 7 h of holding. The corresponding parameters recorded at zero hour of preservation were 83.89±1.25, 89.22±1.29 and 88.78±1.35%, which decreased significantly with increase in hour of preservation and recorded to be 66.39±2.17, 70.78±1.83 and 75.83±1.73% at 96 h of preservation in semen held for 5 h. All the 3 sperm parameters were significantly higher in semen without removal of seminal plasma, i.e., non-removal than in 50, 75 and 100% removal of seminal plasma. The mean sperm motility, live sperm count and intact acrosome recorded were 66.39±2.17, 71.39±1.36 and 70.61±1.22% at 96 h of preservation without removal of seminal plasma.